Occupational Safety and Health (OSH) Practices and Its Influenced Factor - Review OSH in Malaysia - Dafit Feriyanto; S.S. Abdulmalik; Supaat Zakaria (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2020)
High occupational accident in Malaysia as reported by Department of Occupational Safety and Health (DOSH) Malaysia shows the urgently applied a occupational safety and health (OSH) practices in workplaces. This study purposed to review the OSH practices in Malaysia and its influence factor. The factor of that influence to accident cases, good OSH practice and OSH system and framework as well as agencies that has authority with OSH was briefly explained. Factor that influence the accident was consists of stress and fatigue, unsafe act, machinery/tools, design of workplace and training procedure, factor that influenced to achieve good OSH practices was consists of training, safe work procedure, consultation, reporting safety, management commitment and injury management, several OSH agencies that has been developed in Malaysia such as NIOS, NCOSH, DOSH and SOCSO as program in the institution. Institution contribute an important factor due to in institution teach a fundamental of OSH that may applied in the workplaces.